LITERASI KEBERAGAMAAN ANAK KELUARGA MARJINAL BINAAN KOMUNITAS DI KOTA BOGOR - Unang Wahidin (Sekolah Tinggi Agama Islam Al Hidayah, 2017)
Literacy Religious Children Family Marginal Community Guided in the City of Bogor. This research was conducted in Bogor city in community of foster child of marginal family. The research objectives related to the community are: 1. describing the community profile; 2. describe the model of educational curriculum in the community; 3. describe the learning process in the community; While the research objectives related to the children of the marginal family are: 1. describing and analyzing the religious literacy of the belief dimension; 2. describe and analyze religious literacy the dimensions of religious practice; 3. describe and analyze the religious literacy of the dimensions of religious experience; and 4. to describe and analyze the religious literacy of the dimension of religious knowledge. Grand theory used is about: 1. theory of literacy; 2. religious theory; 3. theories about children, and 4. the theory of the marginal family. While the research method used is qualitative with data collection techniques: 1. active participative observation techniques; 2. structured interview techniques; and 3. documentation techniques. The results of research related to the community as follows: 1. community coaches of marginal family children in the city of Bogor is a social group that has a very important role; 2. educational system curriculum model organized by the community of mentors of marginal family children in Bogor city consists of curriculum components organized in such a way and directed to achieve educational objectives; 3. The learning process of the children of the marginalized families carried out by communities in the city of Bogor has been in accordance with the management of regular learning. While the results of research related to the children of the marginal family as follows: 1. the children of the marginal family believe all the get along contained in the pillars of faith; 2. the child of the marginal family is capable of carrying out the practices of the religious teachings he or she believes in; 3. children of marginal families of the majority have religious experience; and 4. the majority of the children of the marginal family have knowledge of the religion they follow.Â Keywords: Literacy, Religious, Children Family Marginal, Community Guided.